dose-response relation between aerobic exercise and visceral fat reduction: systematic review of clinical trials [Erratum: 2008 Feb., v. 32, no. 2, p. 395.] - Ohkawara, K; Tanaka, S; Miyachi, M; Ishikawa-Takata, K; Tabata, I (International Journal of Obesity, 2007)
Objective: It has been suggested that exercise has preferential effects on visceral fat reduction. However, the dose–response effect remains unclear because of limited evidence from individual studies. The purpose of this study was to systematically review the current literature to establish whether reduction of visceral fat by aerobic exercise has a dose–response relationship. Methods: A database search was performed (PubMed, 1966–2006) with appropriate keywords to identify studies exploring the effects of aerobic exercise as a weight loss intervention on visceral fat reduction. Visceral fat reduction was expressed as the percentage of visceral fat change per week (%ΔVF/w). The energy expenditure by aerobic exercise was expressed as ∑(metabolic equivalents × h per week (METs·h/w)). Results: Nine randomized control trials and seven non-randomized control trials were selected. In most of the studies, the subjects performed aerobic exercise generating 10 METs·h/w or more. Among all the selected groups (582 subjects), visceral fat decreased significantly ( P <0.05) in 17 groups during the intervention, but not in the other 4 groups. There was no significant relationship between METs·h/w from aerobic exercise and %ΔVF/w in all the selected groups. However, when subjects with metabolic-related disorders were not included (425 subjects), METs·h/w from aerobic exercise had a significant relationship with %ΔVF/w ( r =−0.75). Moreover, visceral fat reduction was significantly related to weight reduction during aerobic exercise intervention, although a significant visceral fat reduction may occur without significant weight loss. Conclusion: These results suggest that at least 10 METs·h/w in aerobic exercise, such as brisk walking, light jogging or stationary ergometer usage, is required for visceral fat reduction, and that there is a dose–response relationship between aerobic exercise and visceral fat reduction in obese subjects without metabolic-related disorders.